Β‐1 tubulin R307H SNP alters microtubule dynamics and affects severity of a hereditary thrombocytopenia. (22nd January 2015) - Basciano, P. A.; Matakas, J.; Pecci, A.; Civaschi, E.; Cagioni, C.; Bompiani, N.; Burger, P.; Christos, P.; Snyder, J. P.; Bussel, J.; Balduini, C. L.; Giannakakou, P.; et al.
Summary Background Single nucleotide polymorphisms (SNPs) in platelet‐associated genes partly explain inherent variability in platelet counts. Patients with monoallelic Bernard Soulier syndrome due to the Bolzano mutation (GPIBA A156V) have variable platelet counts despite a common mutation for unknown reasons. Objectives We investigated the effect of the most common SNP (R307H) in the hematopoietic‐specific tubulin isotype β‐1 in these Bernard Soulier patients and potential microtubule‐based mechanisms of worsened thrombocytopenia. Patients/Methods Ninety‐four monoallelic Bolzano mutation patients were evaluated for the R307H β‐1 SNP and had platelet counts measured by three methods; the Q43P SNP was also evaluated. To investigate possible mechanisms underlying this association, we used molecular modeling of β‐1 tubulin with and without the R307H SNP. We transfected SNP or non‐SNP β‐1 tubulin into MCF‐7 and CMK cell lines and measured microtubule regrowth after nocodazole‐induced depolymerization. Results We found that patients with at least one R307H SNP allele had significantly worse thrombocytopenia; manual platelet counting revealed a median platelet count of 124 in non‐SNP patients and 76 in SNP patients (both ×109 L−1; P < 0.01). The Q43P SNP had no significant association with platelet count. Molecular modeling suggested a structural relationship between the R307H SNP and microtubule stability via alterations in the M‐loop of β tubulin; in vitro microtubule recovery assays revealed that cells transfected with R307H SNP β‐1 had significantly impaired microtubule recovery. Conclusions Our data show that the R307H SNP is significantly associated with the degree of thrombocytopenia in congenital and acquired platelet disorders, and may affect platelets by altering microtubule behavior.